Long Acting Reversible Contraceptive Practices Among Mothers in Coastal Areas of Bangladesh - Absar, Tanveer UL; Nurunnabi, Mohammad; Haque, Md Amdadul; Begum, Afroza (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Long Acting Reversible Contraceptive (LARC) use helps women prevent unplanned pregnancies, space births, and balance work and family life, while large families increase their burden with added household responsibilities and financial pressure. The objective of this research is to evaluate the status of LARC use among mothers of reproductive age in the coastal areas of Bangladesh. Materials and methods: This cross-sectional study was conducted among married women of reproductive age (1549) in Potenga and Shitakundo, Chittagong, Bangladesh, from January to December 2019. It targeted 196 purposively selected mothers aged 18-49 with at least one child over one year old. Results: The respondents' mean age was 28.4±5.4 years, while their husbands' mean age was 36.2±6.6 years. The majority of respondents (53.1%) used oral contraceptive pills, followed by condoms (22.4%) injectables (8.7%) IUDs (8.2%) and implants (7.7%). Most respondents had their first childbirth before age 20 (68.3%). About 58.7% were aware of LARC, with injectables being the most recognized method (51.2%). While 75% did not use LARC, 59.2% expressed an intention to use it in the future. LARC use was significantly associated with the respondent's and husband's age (p<0.05), with older age groups showing higher usage. Conclusion: The study revealed that oral contraceptive pills were the most widely used method, followed by condoms and injectables. Although most respondents were aware of LARC, only a quarter used it, with injectables being the most common. JCMCTA 2025 ; 36 (1) : 164-170